Technological, organisational, and environmental factors affecting the adoption of blockchain-based distributed identity management in organisations - Mulaji, Sarah Mulombo (Department of Information Systems, 2023)
Background: Blockchain is a disruptive technology with the potential to innovate businesses. Ignoring or resisting it might result in a competitive disadvantage for organisations. Apart from its original financial application of cryptocurrency, other applications are emerging, the most common being supply chain management and e-voting systems. However, there is less focus on information and cybersecurity applications, especially from the enterprise perspective. This research addresses this knowledge gap, focussing on its application of distributed identity management in organisations. Objectives: The main objective is to investigate technological, organisational, and environmental (TOE) factors affecting the adoption of blockchain-based distributed identity management (BDIDM) in organisations to determine the most critical factors. Secondary objectives include determining whether the blockchain type affects BDIDM adoption and whether the TOE-BDIDM model measuring the phenomenon is effective and appropriate. But given the relative newness of blockchain, the initial goal consists of intensively exploring the topic to understand the practicality of adopting BDIDM in organisations and establishing whether claims made around it are factual than just due to the blockchain hype. Methodology: The study uses meta-synthesis to explore the topic, summarising 69 papers selected qualitatively from reputed academic sources. The study then surveys 111 information and cybersecurity practitioners selected randomly in South African organisations to investigate the TOE factors affecting BDIDM adoption. To do so, it utilises an online questionnaire rooted in an adapted TOE model called TOE-BDIDM as a data collection instrument. The analysis of this primary data is purely quantitative and includes (i) Structural Equation Modelling (SEM) of the measurement model, i.e. confirmatory factor analysis (CFA); (ii) binary logistics regression analysis; and (iii) Chi-Square tests Results: Meta-synthesis revealed theoretical grounds underlying claims made around the topic while spotting diverging views about BDIDM practicality for the enterprise context. It also identifies the TOE theory as more suitable to explain the phenomenon. Binary logistics regression modelling reveals that TOE factors do affect BDIDM adoption in organisations, either positively or negatively. The factors predict BDIDM adopters and non-adopters, with Technology Characteristics being the most critical factor and the most that could predict BDIDM non-adopters. Organisation Readiness was the second critical factor, the most that could predict BDIDM adopters. Overall, TOE-BDIDM effectively predicted 92.5% of adopters and 45.2% of non-adopters. CFA indicates that TOE-BDIDM appropriateness for investigating the phenomenon is relatively fair. The Chi-Square tests reveal a significant association between Blockchain Type and BDIDM adoption. Implications: The discussion highlights various implications of the above findings, including the plausibility of the impartiality of typical privacy-preserving BDIDM models like the Selfsovereign identity: The majority of respondents preferred private permissioned blockchain, which tends to be centralised, more intermediated, and less privacy-preserving. The rest implications relate to the disruptiveness nature of BDIDM and the BDIDM adoption being more driven by technological than organisational or environmental factors. The study ends by reflecting on the research process and providing fundamental limitations and recommendations for future research